P-212 Hospice walks for health – introducing a 'walking for health' service at a pro-active hospice. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - MacKinnon, Nicola; Herman, Chris; Baldwin, Diane
Abstract : Background: Following a recent relaunch of the user group at the hospice, users requested the opportunity to participate in regular walks linked to the hospice. Armed with this request we designed a service to complement this and three other key considerations: Increasing evidence that people benefit both physically and psychologically from pursuing as active a lifestyle as possible The hospice is located by two beautiful lakes in an area with a network of well–maintained footpaths There is an already established national 'Walking for Health' (WfH) programme across the city but service users did not have the confidence to use the other walks. Aims: To work in collaboration with our staff, volunteers, local council and users to develop a cost-effective, regular programme to empower service users to be physically active. Methods: Volunteers were recruited, attended training organised by the local Council and were supported by the hospice team to start a weekly WfH program based at the hospice. The walks finish at the main hospice lounge with refreshments and opportunity to socialise. A service user who attends the walks designed a questionnaire to gain qualitative feedback about the walks. Results: Within six weeks, seven patients have regularly attended the weekly walks. Patients describe the benefits of attending the walks as 'companionship, togetherness, friendships, confidence, fitness, strength and stamina'. One patient said, ' I can walk further every week, now I can manage two miles '. Conclusions: Within six weeks, having worked in collaboration with our local Council to have seen six patients and two volunteers go for an hour long walk every week is something to celebrate and share. The Council are now planning to promote the walk in their WfH publications. We now plan to increase the range of these walks and promote them to all users of our services.